2022
DOI: 10.1111/jonm.13624
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the risk of burnout among nurses during the first wave of the COVID‐19 pandemic in Belgium: A cross‐sectional study

Abstract: Aims To estimate the prevalence of burnout risk among nurses during the peak of the first wave of the COVID‐19 pandemic in Belgium and to identify risk groups and protective and risk factors. Background Nurses are at high risk of burnout, and this can have negative consequences for them, patients and health care systems. The pandemic may have changed their working conditions and increased their risk of burnout. Methods The risk of burnout was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…During the COVID-19 pandemic, burnout was found to be higher in physicians and nurses than in other health care workers. 51 - 54 The findings of the present study showed that burnout is negatively related to work engagement. Findings from a survey of 212 health care workers in a Norwegian hospital found that emotional exhaustion had direct effects on job attitudes (job satisfaction and organizational engagement).…”
Section: Discussionmentioning
confidence: 51%
“…During the COVID-19 pandemic, burnout was found to be higher in physicians and nurses than in other health care workers. 51 - 54 The findings of the present study showed that burnout is negatively related to work engagement. Findings from a survey of 212 health care workers in a Norwegian hospital found that emotional exhaustion had direct effects on job attitudes (job satisfaction and organizational engagement).…”
Section: Discussionmentioning
confidence: 51%
“…Additionally, our study was conducted during the COVID‐19 pandemic, a period during which frontline nurses are facing significant difficulties in carrying out their nursing roles and responsibility. Published studies on burnout during the COVID‐19 pandemic reported burnout's influence on nurses' intention to leave (de Cordova et al, 2022 ), burnout during the first wave of the pandemic (Galanis et al, 2021 ; Khan et al, 2022 ), burnout on quality patient care (Kakemam et al, 2021 ), burnout and the affective aspect of nurses (Falatah & Alhalal, 2022 ), burnout's burden to nurses' roles (Kishi et al, 2022 ) and burnout's relationship to self‐efficacy (Lim et al, 2022 ). None of these published studies focused on the moderating effect of burnout on nurses' professionalism, values and competence.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of COVID-19 on the risk of burnout and intention-to-leave the job and the profession seems to be increased among ICU nurses compared to before the pandemic and after the first wave (Bruyneel et al, 2021b;Butera et al, 2021;Vermeir et al, 2018). This can be explained by several elements including the lack of personal protective equipment, fear of being contaminated, increased mortality rates compared to normal, successive waves, societal expectations, and accumulation over time (Bruyneel et al, 2021b;Khan et al, 2022;LeClaire et al, 2022;Moradi et al, 2021). Hospitals have implemented, in a variable and heterogeneous way, several internal measures (e.g., psychologists, debriefing, meditation) which may have influenced the results with ICU nurses in Belgium (Paquay et al, 2022;Servotte et al, 2020;Van Den Heede et al, 2022).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%